Examining the Position of Women in Traditional Polygamy: Insights from Islamic Jurisprudence in the Cultural Context of East Flores - Prakon, Abdu Ihram; Siti Aisyah; Fauzan, Ahmad (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
The position of women in polygamous marriages within Watobuku Village, East Solor, and East Flores, has been observed to strongly reflect the influence of prevailing cultural, tradition, and local values shaping community. This study aims to elucidate the potential mistreatment of women within polygamous marriages by comparing perspectivess of customary law and Islamic law in a sociological framework. This aim was achieved trough the application of qualitative research methodologies, such as observation, in-depth interviews, and documentation analysis. The results obtained from this investigation showed that despite the correspondence of male conduct with certain aspects of Islamic law in polygamous settings, the implementation often lacks fairness, leading to discrimination against women. To address this challenge, it becomes essential to carry out stringent law enforcement with the specific aim of safeguarding the positions held by women, specifically in polygamous unions within the Watobuku Village community. Furthermore, within this context, fostering mutual understanding and responsibility between male and female partners is crucial. It is also important to encourage men, particularly those already married, to appreciate their existing partners and avoid seeking additional spouses without due consideration. In this study, it was suggested that if a husband desires to remarry, he should follow the path of divorcing the first wife before pursuing another marriage. This method was recommended because of its potential to prevent discriminatory practices and uphold justice for women within the context of polygamous marriages.